Association of a 3′ untranslated region polymorphism in proprotein convertase subtilisin/kexin type 9 with HIV viral load and CD4+ levels in HIV/hepatitis C virus coinfected women. (28th November 2017) - Kuniholm, Mark H.; Liang, Hua; Anastos, Kathryn; Gustafson, Deborah; Kassaye, Seble; Nowicki, Marek; Sha, Beverly E.; Pawlowski, Emilia J.; Gange, Stephen J.; Aouizerat, Bradley E.; Pushkarsky, Tatiana; Bukrinsky, Michael I.; et al.
Abstract : Objective: To assess variation in genes that regulate cholesterol metabolism in relation to the natural history of HIV infection. Design: Cross-sectional and longitudinal analysis of the Women's Interagency HIV Study. Methods: We examined 2050 single nucleotide polymorphisms (SNPs) in 19 genes known to regulate cholesterol metabolism in relation to HIV viral load and CD4 + T-cell levels in a multiracial cohort of 1066 antiretroviral therapy-naive women. Results: Six SNPs were associated with both HIV viral load and CD4 + T-cell levels at a false discovery rate of 0.01. Bioinformatics tools did not predict functional activity for five SNPs, located in introns of nuclear receptor corepressor 2, retinoid X receptor alpha ( RXRA ), and tetratricopeptide repeat domain 39B. Rs17111557 located in the 3′ untranslated region of proprotein convertase subtilisin/kexin type 9 ( PCSK9 ) putatively affects binding of hsa-miR-548t-5p and hsa-miR-4796–3p, which could regulate PCSK9 expression levels. Interrogation of rs17111557 revealed stronger associations in the subset of women with HIV/hepatitis C virus (HCV) coinfection ( n  = 408, 38% of women). Rs17111557 was also associated with low-density lipoprotein cholesterol levels in HIV/HCV coinfected (β: −10.4; 95% confidence interval: −17.9, −2.9; P  = 0.007), but not in HIV monoinfected (β:1.2; 95% confidence interval: −6.3, 8.6; P  = 0.76) women in adjusted analysis. Conclusion: PCSK9 polymorphism may affect HIV pathogenesis, particularly in HIV/HCV coinfected women. A likely mechanism for this effect is PCSK9 -mediated regulation of cholesterol metabolism. Replication in independent cohorts is needed to clarify the generalizability of the observed associations. Abstract : Supplemental Digital Content is available in the text